2005
DOI: 10.1149/1.2052019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight of Polyethylene Glycol on Microvia Filling by Copper Electroplating

Abstract: The influence of the molecular weight ͑Mw͒ of polyethylene glycol ͑PEG͒ on the microvia filling by copper electroplating was demonstrated and examined by cross-sectional images using an optical microscope. The electrochemical behavior of PEG of different molecule weights in the copper electroplating was characterized by galvanostatic measurement. In the presence of excess Cl − , the surface coverage of PEG of various Mw adsorbed on the copper surface was characterized by observing the size and distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 40 publications
2
157
0
Order By: Relevance
“…After 800 seconds, another leveler was injected into the electrolyte. 18 The filling performance of various formulas was characterized by a mean potential difference ( η) between the two polarization curves measured with the Cu RDE that was individually operated at 100 rpm and 1000 rpm. It was showed that if the copper plating formulas can perform bottom-up filling of a microvia, then a positive potential difference (i.e., η = E 100rpm −E 1000rpm > 0) occurs.…”
Section: Methodsmentioning
confidence: 99%
“…After 800 seconds, another leveler was injected into the electrolyte. 18 The filling performance of various formulas was characterized by a mean potential difference ( η) between the two polarization curves measured with the Cu RDE that was individually operated at 100 rpm and 1000 rpm. It was showed that if the copper plating formulas can perform bottom-up filling of a microvia, then a positive potential difference (i.e., η = E 100rpm −E 1000rpm > 0) occurs.…”
Section: Methodsmentioning
confidence: 99%
“…The suppression of deposition rate is also likely due to competition for active sites on the depositing surface by adsorptive PEG molecules [44]. In 2005, Dow et al [6] studied the influence of the molecular weight of PEG, and found that the higher the molecular weight of PEG, the stronger the suppression effect on the deposition rate of Cu. Suppressor adsorbs on the surface of the Cu deposit outside the hole, which can suppress the deposition rate of Cu outside the hole.…”
Section: Suppressormentioning
confidence: 99%
“…In TSV technology, Cu is used to fill the via as an interconnect. There are several matured techniques that can fabricate the Cu wire/interconnect, such as sputtering, evaporation, and electrochemical deposition, among which electrochemical deposition (also known as electroplating) is a cost-effective method capable of making uniform and hole-filling Cu metallization [1,[4][5][6]. In addition to basic constitutes such as sulfuric acid and copper sulphate, it is necessary to add several functional additives in the plating bath to assist or modulate the deposition of Cu atoms on non-planar substrates [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…65 The binding force between TU and PEG could retard the desorption of TU from PEG-covered Cu. Likewise, since the adsorption strength of PEG on the Cu surface increased with molecular weight, 66,67 high-molecular-weight PEG could effectively suppress the desorption of TU.…”
Section: [Tumentioning
confidence: 99%